2021
DOI: 10.1039/d1ee02567h
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-solid-state electrolytes utilizing the ionic liquid family for rechargeable batteries

Abstract: The advent of solid-state electrolytes has unearthed a new paradigm of next-generation batteries endowed with improved electrochemical properties and exceptional safety. Amongst them, Li-stuffed garnet type oxides, sulfides, and NASICON...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 349 publications
0
38
0
Order By: Relevance
“…Thus, it is necessary to develop a simple and efficient strategy to improve the compatibility of the solid/solid interfaces in all solid-state batteries. Recent studies have proposed several novel methods, such as modifying solid-state electrolytes using ionic liquids (ILs) to assemble a pseudo-solid-state battery. , ILs not only have high ionic conductivity, high thermal stability, and high chemical stabilities but also improve the ionic conductivity and the electrochemical stability of the selected electrolytes. Li et al showed an effective method by incorporating an ionic liquid electrolyte ((PYR/Na)­TFSI) as an interlayer to form a stable SEI to improve the compatibility of the Na metal and sulfide-based solid electrolyte interface .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary to develop a simple and efficient strategy to improve the compatibility of the solid/solid interfaces in all solid-state batteries. Recent studies have proposed several novel methods, such as modifying solid-state electrolytes using ionic liquids (ILs) to assemble a pseudo-solid-state battery. , ILs not only have high ionic conductivity, high thermal stability, and high chemical stabilities but also improve the ionic conductivity and the electrochemical stability of the selected electrolytes. Li et al showed an effective method by incorporating an ionic liquid electrolyte ((PYR/Na)­TFSI) as an interlayer to form a stable SEI to improve the compatibility of the Na metal and sulfide-based solid electrolyte interface .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the ability to sustain stable operations at intermediate temperatures (above room temperatures) and tolerance to spontaneous temperature fluctuations without compromising safety are expected to become key requisites for future battery applications . However, contemporary commercialized LIBs, which generally utilize carbonate-based organic electrolytes, are known to be unsuitable for elevated-temperature operation because of diminished performance caused by electrolyte degradation and potential fire hazards. These safety concerns have generated traction among ionic liquid (IL) electrolytes which have been deemed to have high resilience to temperature elevations and fluctuations attributed to their nonflammability and low volatility. ,, Furthermore, intermediate-temperature operations have been found to ameliorate the performance of IL electrolytes, thus creating a new avenue for utilizing the ubiquitous waste heat in daily activities. ,, …”
Section: Introductionmentioning
confidence: 99%
“…34−36 These safety concerns have generated traction among ionic liquid (IL) electrolytes which have been deemed to have high resilience to temperature elevations and fluctuations attributed to their nonflammability and low volatility. 33,37,38 Furthermore, intermediate-temperature operations have been found to ameliorate the performance of IL electrolytes, thus creating a new avenue for utilizing the ubiquitous waste heat in daily activities. 33,39,40 It is evident that pseudocapacitive materials, particularly Nb 2 O 5 , represent an exquisite class of energy materials that promise to revolutionize battery capabilities beyond the contemporary scopes of battery performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Our group proposed an interlayer LAGP//Li metal based on polycarbonate (QPAC) LAGPLiTFSI:pyr13TFSI, showing good stability under a current of 0.3C and 50 °C. Hwang et al recently resumed the progress of a pseudo-solid-state electrolyte by mixing ceramic and ionic liquids: the authors underlined the importance of understanding the properties of interfaces. The literature review shows a lack of knowledge about the reactions occurring between ceramic and ionic liquids although they are used regularly together in several reports showing good electrochemical performances.…”
Section: Introductionmentioning
confidence: 99%